Sosialisasi Pencegahan Perundungan (Bullying) pada Siswa (SMA Dharma Karya) - Meliza; Hanif Hardianto; Megafury Apriandhini; Purwaningdyah Murti Wahyuni; Sri Wahyu Krida Sakti; Nadia Nurani Isfarin; A.Rachmat Wirawan; Madiha Dzakiyyah Chairunnisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Violence in the world of education is a shared responsibility, not only the responsibility of the school but the community (parents) also have an important role in preventing violence in the world of education. The problem of bullying is a problem that often occurs in educational institutions and at SMA Dharma Karya there is still bullying between students, although the bullying does not amount to serious cases, but students' understanding of bullying is very necessary so that students know the dangers of these actions. the. The implementation of activities was carried out with initial coordination, then the socialization was carried out on June 9 2023 and monitoring of activities was carried out on August 22 2023. The results of the socialization on bullying prevention among Dharma Karya High School students showed that 75 people had experienced bullying, 102 people felt that they were not. have experienced bullying.